(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
This work is devoted to the formation and development of linguopoetics as a new branch of philology, as well as its methodology. The purpose of the study is to try to establish whether linguopoetics is an independent philological discipline or whether it is a simple combination of linguistic stylistics and literary criticism.